Cholesterol access in cellular membranes controls Hedgehog signaling - Radhakrishnan, Arun (Nat Chem Biol, 2020)
The Hedgehog (Hh) signaling pathway coordinates cell–cell communication in development and regeneration. Defects in this pathway underlie diseases ranging from birth defects to cancer. Hh signals are transmitted across the plasma membrane by two proteins, Patched 1 (PTCH1) and Smoothened (SMO). PTCH1, a transporter-like tumor-suppressor protein, binds to Hh ligands, but SMO, a G-protein-coupled-receptor family oncoprotein, transmits the Hh signal across the membrane. Recent structural, biochemical and cell-biological studies have converged at the surprising model that a specific pool of plasma membrane cholesterol, termed accessible cholesterol, functions as a second messenger that conveys the signal between PTCH1 and SMO. Beyond solving a central puzzle in Hh signaling, these studies are revealing new principles in membrane biology: how proteins respond to and remodel cholesterol accessibility in membranes and how the cholesterol composition of organelle membranes is used to regulate protein function.